Transcranial Direct Current Stimulation to the Right Temporoparietal Junction for Social Functioning in Autism Spectrum Disorder: A Case Report. Issue 1 (March 2018) - Esse Wilson, Joan; Quinn, Davin K.; Wilson, J. Kevin; Garcia, Christopher M.; Tesche, Claudia D.
Abstract : Objectives: While there is evidence of improved social functioning after applying transcranial direct current stimulation (tDCS) at the right temporoparietal junction (rTPJ) in individuals who are healthy, no current studies have investigated the use of tDCS at the rTPJ to improve social functioning in individuals with autism spectrum disorder (ASD). This case investigates the use of tDCS applied to the rTPJ to target social functioning in a high-functioning adult with ASD. Methods: The authors present a case of an 18-year old patient with ASD treated successfully with tDCS; 1.5 mA of tDCS was applied once a day for 30 minutes for 8 consecutive days with the anode electrode over rTPJ (CP6 in the 10/10 electroencephalogram system) and the cathode electrode placed on the ipsilateral deltoid. Behavioral outcome was assessed using the Autism Treatment Evaluation Checklist prior to tDCS, after the final tDCS session, and at 2 months after tDCS. An additional, informal follow-up was also made 1 year after tDCS. Results: Autism Treatment Evaluation Checklist showed substantial improvement in social functioning from baseline to post-tDCS, which was maintained at 2 months. The patient also reported lessened feelings of anger and frustration over social disappointments. Informal follow-up 1 year after stimulation indicates that the patient continues to maintain many improvements. Conclusions: Anodal tDCS to the rTPJ may represent an effective treatment for improving social functioning in ASD, with a larger clinical trial needed to validate this effect.